Analysis of Sediment Characteristics and Sedimentation Rate of the Noling River, Luwu Regency - Juliandro Juliandro; Muhammad Syafa'at S Kuba; Farida Gaffar; Ismail Pawara (Universitas Sulawesi Barat, 2025)
The Noling River plays an important role in the lives of the surrounding communities; however, it faces sedimentation problems that lead to riverbed aggradation, infrastructure disturbances, and reduced flow capacity. This study aims to determine the sediment characteristics and the rate of sedimentation in the Noling River, Luwu Regency. Sediment samples were collected from the midstream section of the river and analyzed in the laboratory to determine grain size distribution, specific gravity, and physical characteristics of the sediment. The results show that the Noling River sediment is dominated by sand (57.4%), gravel (31.8%), and silt/clay (10.9%), with a sediment classification of sandy clay. The sedimentation rate was calculated using both direct measurement and empirical approaches (Meyer-Peter and Duboys methods). The average suspended sediment load was found to be 5,251.97 tons/month, while the bed load reached 1,102.91 tons/month. The flow velocity, which exceeds the sediment fall velocity, indicates that sediment transport occurs actively. The findings of this study are expected to serve as a reference for better river management and future sedimentation mitigation efforts.